Research themes of family and community physicians in Brazil - Fontenelle, Leonardo Ferreira; Rossi, Stephani Vogt; Oliveira, Miguel Henrique Moraes de; Brandão, Diego José; Sarti, Thiago Dias (AtoZ: novas práticas em informação e conhecimento, 2023)
Introduction: Research capacity in primary care varies worldwide, and bibliographic databases such as MEDLINE, Scopus and Web of Science do not index most primary care research coming from Latin America. Our objective was to investigate the research themes of family and community physicians in Brazil, and to correlate the articles’ research themes with their authors’ trajectories in postgraduate education. Methods: we compiled a national list of family and community physicians, retrieved their curricula from the Lattes Platform, compiled a list of journal articles, and obtained their keywords from LILACS and MEDLINE. Treating journal articles and their keywords as the two node types in a bipartite network, we derived research themes using the dual-projection algorithm, combining the Leiden algorithm with hierarchical clustering. Results: We found two research themes to be the largest, most developed, and most central ones: human health and primary care. Authors with a master’s or PhD in collective health (public health, epidemiology, and social sciences and humanities in health) were as likely as those with no postgraduate degree to publish articles on primary care. On the other hand, authors with a postgraduate degree in medicine were more likely to publish articles on human health. Conclusions: After discussing the findings in light of previous research and methodological aspects, we conclude there’s a relative divide between primary care and clinical research, and the highlight policy implications.